Influence of dredging activities on the ichthyofauna of the Paranaguá Estuarine Complex, Paraná State - Parizotti, Tuan Duarte; Cattani, André Pereira; Santos, Lilyane De Oliveira; Ferreira, Tábata Larissa; Spach, Henry Louis (Arquivos de Ciências do Mar, 2015)
The estuarine environment is an important reproduction and nursery area for many fish species. This environment is under constant impact by human activities. The dredging in Ponta do Poço, Paranaguá Estuary (southern Brazil), offers an opportunity to assess the ichthyofauna’s differences in this location and in a place without dredging. The ichthyofauna were collected using bottom trawlnets in two sectors, dredged (D) and not-dredged (N-D) with nine sampling spots in each sector. The samplings occurred monthly from March, 2012 to August, 2013. In total, 3283 fish belonging to 63 species and 27 families were collected. Pomadasys corvinaeformis was the most abundant species and represents 46.5% of the total capture. The not- dredged sector presented higher values of abundance (N-D = 2808; D = 475), biomass (N-D = 66 kg; D = 27 kg), diversity (N-D = 51; D = 45) and dominance than the Dredged sector. The abundance and biomass comparison show that the two sectors have a moderated disturbance. The food guilds analyses showed that the that predate on zoobenthos are the responsible for the differences between two sectors and these species are more abundant in the Not-dredged sector.